Malnutrition in children : methodical recommendations - Bulich, I. M.; Rakovska, L. O.; Буліч, Ілона Миколаївна; Раковська, Людмила Олександрівна (Kharkiv : V. N. Karazin Kharkiv National University, 2019)
Methodical recommendations are devoted to a global medical problem in the world – protein-energy deficiency in children. The classification, diagnostic criteria of malnutritions are presented. Methods of treatment of severe forms of malnutrition are described. Special attention is paid to diet therapy in different phases of the disease. Methodical recommendations are worked out on the basis of the Program of discipline of «Pediatrics» for students of higher medical educational institutions of III–IV levels of accreditation, authorized by Ministry of Health of Ukraine. These recommendations are intended for the 4th year English-speaking medical students.

Методичні рекомендації присвячено глобальній медичній проблемі в світі – білково-енергетичній недостатності у дітей. Наведено класифікацію, діагностичні критерії гіпотрофій. Детально описано методи лікування тяжких форм розладів харчування. Особливу увагу приділено дієтотерапії у різні фази захворювання. Методичні рекомендації розроблено на основі Програми дисципліни «Педіатрія» для студентів вищих медичних навчальних закладів III–IV рівнів акредитації, затвердженої МОЗ України. Дані рекомендації призначені для студентів 4-го курсу медичного факультету англомовного навчання.
Розлади харчування у дітей : методичні рекомендації
Навчальне видання
Keywords: MEDICINE; SOCIAL SCIENCES; protein-energy malnutrition; hypotrophy; marasmus; kwashiocor; diet therapy; білкова-енергетична недостатність; гіпотрофія; маразм; квашіокор; дієтотерапія